The implicated clinical factors for outcomes in 304 patients with salivary duct carcinoma: Multi‐institutional retrospective analysis in Japan. Issue 6 (29th March 2022) - Kusafuka, Kimihide; Sato, Yoko; Nakatani, Eiji; Baba, Satoshi; Maeda, Matsuyoshi; Yamanegi, Koji; Ueda, Kaori; Inagaki, Hiroshi; Otsuki, Yoshiro; Kuroda, Naoto; Suzuki, Kensuke; Iwai, Hiroshi; et al.
Abstract: Background: Salivary duct carcinoma (SDC) is a high‐grade salivary malignancy that frequently occurs as the carcinomatous component of carcinoma ex pleomorphic adenoma. We herein examined the clinical factors affecting outcomes in a large cohort of SDC. Methods: We selected 304 SDC cases and investigated clinical characteristics and the factors affecting outcomes. Results: The median age of the cases examined was 68 years, the most common primary site was the parotid gland (238 cases), and there was a male predominance (M/F = 5:1). Outcomes were significantly worse when the primary tumor site was the minor salivary glands (SG) than when it was the major SG. Outcomes were also significantly worse in pN(+) cases (161 cases) than in pN0 cases, particularly those with a metastatic lymph node number ≥11. The cumulative incidence of relapse and distant metastases was significantly higher in stage IV cases than in stage 0–III cases. Conclusions: The absolute number of lymph node metastases, higher stages, and the minor SG as the primary tumor site were identified as factors affecting the outcome of SDC.